STRATEGI DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT - Saputra, Trio; Sufi, Wasiah (LLDIKTI Wilayah X, 2018)
This research is expected to reach the service oriented library to the visitor. With the strategies undertaken to overcome the obstacles and shortcomings that occur. This research uses descriptive qualitative research methods and data collection techniques using observation, interviews, documentation. Informants in this research is the head and staff of UPT Library archive and documentation of Bukit Batu district Bengkalis District and visitors and community leaders in the library environment. In the data analysis used descriptive method that describes the Theory with the objective conditions and information on the results of interviews combined with the data of researchers in accordance with the results of field observation. Library Management at UPT Library Archives and Documentation District Bukit Batu Bengkalis Regency is not running optimally. Factors that become obstacles in providing services to visitors such as facilities and infrastructure that are not complete, the number and quality of human resources Librarian is not adequate. Penelitian ini diharapkan tercapainya pelayanan perpustakaan yang berorientasi kepada pengunjung. Dengan strategi-strategi yang dilakukan dapat mengatasi hambatan dan kekurangan yang terjadi. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dan teknik pengumpulan data dengan menggunakan observasi, wawancara, dokumentasi. Informan dalam penelitian ini adalah adalah kepala dan pegawai UPT Badan perpustakaan arsip dan dokumentasi kecamatan Bukit Batu Kabupaten Bengkalis dan pengunjung serta tokoh masyarakat dilingkungan perpustakaan. Didalam Analisa data digunakan metode Deskriptif yaitu menggambarkan Teori dengan kondisi objektif serta informasi hasil wawancara digabungkan dengan data peneliti sesuai dengan hasil observasi dilapangan. Pengelolaan Perpustakaan pada UPT Perpustakaan Arsip dan Dokumentasi Kecamatan Bukit Batu Kabupaten Bengkalis tidak berjalan secara optimal. Faktor-faktor yang menjadi kendala dalam memberikan pelayanan kepada pengunjung diantaranya adalah sarana dan prasarana yang tidak lengkap, jumlah dan kualitas SDM Pustakawan yang belum memadai.